Dewatering of faecal sludge with geotextiles: Results from laboratory and bench-scale experiments in Kampala, Uganda - Ziebell, Fritzi; Gold, Moritz; Matovu, Jafari; Maiteki, James; Niwagaba, Charles; Strande, Linda (Sandec/Eawag, 2016)
Worldwide, sanitation needs of 2.7 billion people are met by onsite sanitation technology such as pit latrines and septic tanks (Cairns-Smith et al., 2014). These technologies collect large amounts of faecal sludge (FS). FS is the raw or partially digested, semisolid or slurry resulting from collection, storage or treatment of combinations of excreta and blackwater, with or without greywater that accumulates in these technologies (Strande, 2014). Onsite sanitation technologies can provide adequate and affordable sanitation given that faecal sludge management (FSM) is in place, including collection, transport, treatment and safe enduse or disposal of FS (Dodane et al., 2012; Strande, 2014). Currently, the majority of FS in low-income countries is discharged inadequately or untreated into the urban environment. For example, in Kampala, Uganda, 46% of excreta is not safely managed (Schoebitz et al., 2016). In other East African cities, even less excreta is adequately managed. In Dar Es Salaam, Tanzania, and in Nakuru, Kenya, 57% and 64% of excreta are not safely managed (Brandes et al., 2015; Furlong, 2015). This has significant public and environmental health, and economic implications (Bartram et al., 2010; Boschi-Pinto et al., 2008; Hutton et al., 2004; Mara et al., 2010). In urban areas with reliable water supply and/or high groundwater levels, FS commonly consists of> 95% water (Cofie et al., 2006; Gold et al., 2016; Niwagaba et al., 2014; Seck et al., 2015; Sonko et al., 2014; Strauss et al., 1997). For example, in Kampala it is about 97-99%(Gold et al., submitted; Schoebitz et al., in preparation). This makes FS dewatering one of the most important treatment goals. In addition, water is heavy and thus expensive to transport. This suggests that dewatering can contribute to financial viable FS transport logistics. Drying beds are the most commonly used treatment technology for FS (Dodane et al., 2014). In comparison to other dewatering technologies, drying beds have low capital and operational costs and a low operational complexity. However, they require long dewatering times and produce a treatment product that can have a low resource recovery value (eg high ash content for use as fuels)(Seck et al., 2015).